Characterization of Recharge Mechanisms and Sources of Groundwater Salinization in Ras Jbel Coastal Aquifer (Northeast Tunisia) Using Hydrogeochemical Tools, Environmental Isotopes, GIS, and Statistics - Jamila Hammami Abidi; Boutheina Farhat; Abdallah Ben Mammou; Naceur Oueslati (Journal of Chemistry)
Groundwater is among the most available water resources in Tunisia; it is a vital natural resource in arid and semiarid regions. Located in north-eastern Tunisia, the Metline-Ras Jbel-Raf Raf aquifer is a mio-plio-quaternary shallow coastal aquifer, where groundwater is the most important source of water supply. The major ion hydrochemistry and environmental isotope composition (δ18O, δ2H) were investigated to identify the recharge sources and processes that affect the groundwater salinization. The combination of hydrogeochemical, isotopic, statistical, and GIS approaches demonstrates that the salinity and the groundwater composition are largely controlled by the water-rock interaction particularly the dissolution of evaporate minerals and the ion exchange process, the return flow of the irrigation water, agricultural fertilizers, and finally saltwater intrusion which started before 1980 and which is partially mitigated by the artificial recharge since 1993. As for the stable isotope signatures, results showed that groundwater samples lay on and around the local meteoric water line LMWL; hence, this arrangement signifies that the recharge of the Ras Jbel aquifer is ensured by recent recharge from Mediterranean air masses.